2016
DOI: 10.1021/acs.cgd.5b01495
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Crystal Structure of the First Molecular Polymorph in History

Abstract: Despite being the earliest reported case of polymorphism in a molecular crystal, the unstable form II of benzamide has thus far evaded thorough structural characterization because collection of experimental data at atomic resolution has proven extremely challenging. Using a highly validated computational crystal structure prediction (CSP) method based on dispersion-corrected density functional theory, we correctly predict the stable form I with the lowest energy among all sampled structures and its polytypic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Benzamide I platelike crystals show single-crystal-like selected area electron diffraction (SAED) patterns (projected along [1 11] zone axis) with sharp reflections free of diffuse scattering (Figure 8a), while benzamide II needles show strong diffuse scattering in planes perpendicular to the needle elongation direction (Figures 8b-d;F igure S6). Thel attice periodicity of % 5.2 along the crystal elongation direction is consistent with the orientation of hydrogen-bond tapes in all proposed crystal structures [12] (Figure S3). This direction is also confirmed by the analysis of preferred orientations in powder X-ray patterns collected from an assembly of needles on af lat substrate.B ased on our indexing of PXRD data in P2 1 /c, needles are elongated along [100]*.…”
Section: Angewandte Chemiesupporting
confidence: 82%
See 2 more Smart Citations
“…Benzamide I platelike crystals show single-crystal-like selected area electron diffraction (SAED) patterns (projected along [1 11] zone axis) with sharp reflections free of diffuse scattering (Figure 8a), while benzamide II needles show strong diffuse scattering in planes perpendicular to the needle elongation direction (Figures 8b-d;F igure S6). Thel attice periodicity of % 5.2 along the crystal elongation direction is consistent with the orientation of hydrogen-bond tapes in all proposed crystal structures [12] (Figure S3). This direction is also confirmed by the analysis of preferred orientations in powder X-ray patterns collected from an assembly of needles on af lat substrate.B ased on our indexing of PXRD data in P2 1 /c, needles are elongated along [100]*.…”
Section: Angewandte Chemiesupporting
confidence: 82%
“…[6,7] Despite reasonably good R-factors,the data was burdened with strong preferred orientations of crystallites,c ontributions from amorphous material (aqueous solution), and admixtures of form I.E leven years later, the structure was re-examined using the same experimental data and crystal structure prediction (CSP) methods. [12] It was concluded that the Pba2s tructure had an unreasonably high lattice energy. Instead, two other candidate structures, Fdd2and P2 1 /c,were suggested, which provided low lattice energies and good agreement with the experimental data.…”
Section: Forschungsartikelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature (Thun et al, 2009;Johansson & van de Streek, 2016), the small organic molecule benzamide crystallizes as three different polymorphs, Form I, Form II and Form III. After comparison of the packings of the benzamide entries in the Cambridge Structural Database (CSD, Version 5.37; Groom et al, 2016), one would expect a simple similarity matrix and a dendrogram with three different similarity groups.…”
Section: Packing Similarity Of Crystal Structures Of Benzamidementioning
confidence: 99%
“…Entries 1-4 are from this study and are X-ray structures, entry 5 is from Johansson & van de Streek (2016) and is an X-ray structure, and entry 6 is from Greenberg & Venanzi (1993) and are calculated values. Table 4 Resonance energies of amides 1a-1e calculated using the COSNAR method a .…”
Section: Figurementioning
confidence: 99%